Digital Marketing Capability as a Strategic Driver of Firm Performance: Evidence from Culinary MSMEs in Medan City - Genesis Sembiring; Jenny Halim (Indonesian Journal of Business Analytics, 2025)
This study investigates the influence of Digital Marketing Capability, Organizational Agility, and Human Capital on Firm Performance among culinary MSMEs in Medan City. Using a quantitative approach, primary data were obtained from ninety-seven respondents, including business owners, managers, and employees, through structured questionnaires. The data were analyzed using descriptive statistics and multiple linear regression with SPSS version 25. The findings reveal that Digital Marketing Capability has a positive and significant effect on Firm Performance, while Organizational Agility and Human Capital show no significant effect. Simultaneously, the three variables have a positive impact on firm performance. These results suggest that mastery of digital marketing strategies plays a dominant role in enhancing competitiveness and business success. This study supports the Resource-Based View (RBV) theory, emphasizing that internal digital competence serves as a strategic asset for achieving sustainable firm performance among culinary MSMEs in Medan City.